2010
DOI: 10.1073/pnas.0912585107
|View full text |Cite
|
Sign up to set email alerts
|

Pitx2 prevents susceptibility to atrial arrhythmias by inhibiting left-sided pacemaker specification

Abstract: Atrial fibrillation (AF), the most prevalent sustained cardiac arrhythmia, often coexists with the related arrhythmia atrial flutter (AFL). Limitations in effectiveness and safety of current therapies make an understanding of the molecular mechanism underlying AF more urgent. Genome-wide association studies implicated a region of human chromosome 4q25 in familial AF and AFL, ≈150 kb distal to the Pitx2 homeobox gene, a developmental left-right asymmetry (LRA) gene. To investigate the significance of the 4q25 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
318
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 283 publications
(338 citation statements)
references
References 43 publications
12
318
0
5
Order By: Relevance
“…To gain insight into miRs involved in AF pathogenesis, we performed miR expression profiling using hearts from Pitx2 null/null mutant and wild type, and ChIP-sequencing (ChIP-Seq) using hearts from the Pitx2-Flag allele (16,18), which express Pitx2 with a C-terminal Flag epitope tag ( Fig. 1 A and C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain insight into miRs involved in AF pathogenesis, we performed miR expression profiling using hearts from Pitx2 null/null mutant and wild type, and ChIP-sequencing (ChIP-Seq) using hearts from the Pitx2-Flag allele (16,18), which express Pitx2 with a C-terminal Flag epitope tag ( Fig. 1 A and C).…”
Section: Resultsmentioning
confidence: 99%
“…To determine the miR-17-92 expression pattern in heart, we generated an miR-17-92 bacterial artificial chromosome transgenic LacZ reporter line (20) and compared it with a Pitx2 LacZ knock-in allele (16). In E12.5 hearts, LacZ staining indicated that miR-17-92 is expressed in the outflow tract (OFT), left atrium (LA), coronary sinus, and atrioventricular canal (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5.1) [62,65,66]. Jako potencjalne mechanizmy leżące u podłoża zwiększonego ryzyka AF u nosicieli częstych wariantów genetycznych postuluje się zmiany charakterystyki potencjału czynnościowego komórek przedsionków [67][68][69][70], przebudowę przedsionków oraz zmodyfikowaną penetrację rzadkich defektów genetycznych [61]. Warianty genetyczne mogłyby w przyszłości stać się użyteczne podczas doboru pacjentów do strategii kontroli rytmu serca lub kontroli częstości rytmu komór [71][72][73][74].…”
Section: Skłonność Genetycznaunclassified
“…The gene most closely located to the risk variants encodes the two-domain transcription factor, PITX2. Low expression levels of PITX2 mRNA induce complex left atrial gene expression changes, without apparent structural alter ations, that predispose to AF 19,67 . Thus, altered expression of atrial ion channels as a result of genetic alterations in the atria could be a common path by which subtle genetic changes predispose patients to AF, subsequently influencing the response to antiarrhythmic drugs 68 .…”
Section: Ion-channel Dysfunctionmentioning
confidence: 99%